indonesia Penerapan Media Digital Wayground untuk Meningkatkan Keaktifan Siswa: Dalam pembelajaran bahasa arab tema Amali fi Al-Mustaqbal pada siswa tingkatan 3 Sekolah Menengah Agama Taufikiah Khairiah Al-Halimiah Kedah Malaysia - Amin, Azkiya Rafida (Maliki Interdisciplinary Journal, 2026)
This research was motivated by the low level of student participation in Arabic language learning on the theme Amali fil Mustaqbal among third-level students at Sekolah Menengah Agama Taufikiah Khairiah Al-Halimiah Kedah, Malaysia. Some students tended to be passive during the learning process, making it difficult for the teacher to identify students’ understanding of the material that had been explained. Therefore, this study aimed to improve students’ activeness through the implementation of the digital media Wayground in Arabic language learning. This study used a Classroom Action Research (CAR) method with a qualitative descriptive approach employing the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The subjects of this study were 23 third-level students, and the research was conducted over six meetings within one month. Data collection techniques included observation, learning evaluation using Wayground digital media, and documentation. The results showed that the implementation of Wayground digital media was able to improve students’ activeness in Arabic language learning. Students became more enthusiastic, actively participated in discussions, and were more focused during the learning process. In addition, the use of Wayground also helped teachers identify students’ understanding of the Amali fil Mustaqbal material through interactive quizzes. Therefore, Wayground digital media can be an effective alternative learning medium to improve student activeness in Arabic language learning.